2004
DOI: 10.1029/2003jb002619
|View full text |Cite
|
Sign up to set email alerts
|

Continuous GPS measurements of postglacial adjustment in Fennoscandia: 2. Modeling results

Abstract: [1] Data collected under the auspices of the BIFROST GPS project yield a geographically dense suite of estimates of present-day, three-dimensional (3-D) crustal deformation rates in Fennoscandia [Johansson et al., 2002]. A preliminary forward analysis of these estimates has indicated that models of ongoing glacial isostatic adjustment (GIA) in response to the final deglaciation event of the current ice age are able to provide an excellent fit to the observed 3-D velocity field. In this study we revisit our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
147
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(170 citation statements)
references
References 43 publications
21
147
0
Order By: Relevance
“…Previous studies into these effects include surface mass loading (Clarke et al 2007;van Dam et al , 2001), plate tectonics (Larson et al 1997;Kogan and Steblov 2008) and GIA (e.g. Milne et al 2004). However, there are some doubts in the quality of the TRF used in these early studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies into these effects include surface mass loading (Clarke et al 2007;van Dam et al , 2001), plate tectonics (Larson et al 1997;Kogan and Steblov 2008) and GIA (e.g. Milne et al 2004). However, there are some doubts in the quality of the TRF used in these early studies.…”
Section: Introductionmentioning
confidence: 99%
“…Regional GIA models with 1D Earth structure (e.g. Milne et al 2004) may be tuned to represent both lateral and vertical velocities, but full 3D variable Earth structure is necessary for accurate modelling throughout the global domain (Latychev et al 2005). …”
Section: Creating the Modelmentioning
confidence: 99%
“…These investigations have shown that it is not yet possible to uniquely constrain Earth's viscosity structure for the Fennoscandian region. Such studies, however, Milne et al (2001Milne et al ( , 2004, namely; lithospheric thickness is varied from 71 to 120 km, upper mantle viscosity from 0.05 9 10 21 to 5 9 10 21 Pas and lower mantle viscosity from 10 21 to 50 9 10 21 Pas.…”
Section: Earth Model Sensitivity Test and Determining A Best-fit Modelmentioning
confidence: 99%
“…In the following we describe each component in order; the model setup is similar to that used in the analysis of Milne et al (2001) and Milne et al (2004).…”
Section: Glacial Isostatic Adjustment Modelingmentioning
confidence: 99%
See 1 more Smart Citation